Insights into the role of earthworms on the optimization of microbial community structure during vermicomposting of sewage sludge by PLFA analysis. (September 2018) - Zhao, Chunhui; Wang, Yong; Wang, Yue; Wu, Feijie; Zhang, Jiageng; Cui, Ruiyi; Wang, Liguo; Mu, Hui
Graphical abstract: Highlights: Optimization effect of earthworms in vermicomposting was studied by PLFA profiles. Earthworm activity expanded the microbial community diversity in vermicomposting. Percentages of fungi and protozoa were increased due to the presence of earthworms. The burrowing action of earthworms improved aerobic condition of vermicomposting. Abstract: In this study, the influences of earthworms on the structure of microbial community as well as the metabolic function in vermicomposting (VPs, with earthworms) for excess sludge stabilization were investigated. Comparison between the dynamic variation of PLFA profiles in VPs and common composting (CPs, with no earthworms) was conducted. The Shannon index was increased in VPs, while it was decreased in CPs with time, indicating earthworm activity enhanced microbial community diversity. The fungal and protozoal biomasses were significantly increased in VPs compared with CPs. Further researches by principal component analysis (PCA) indicated that earthworms benefited certain microorganisms containing biomarkers of 18:1ω9c, 18:3ω3, 18:3ω6, 20:1ω9, 20:2ω6 and 20:3ω6. Moreover, the ratios of monounsaturated to branched PLFAs in VPs were larger than those in CPs, suggesting the aeration condition was promoted by the burrowing behaviors of earthworms and therefore facilitated the growth and propagation of aerobic microorganisms, such as protozoa. Those results indicated that earthworm activity led to the general optimization of vermicomposting for excess sludge stabilization.